FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MASYARAKAT TERHADAP PEMBIAYAAN MITRA EMAS BANK JAWA BARAT SYARIAH KANTOR CABANG PEMBANTU JEMBATAN MERAH, KOTA BOGOR, JAWA BARAT - Mulniasari, Nina; Trihantana, Rully; Kusumaningrum, Ria (SAHID BANKING JOURNAL, 2024)
This study aims to determine and analyze the influence of factors consisting of cultural, social, personal, psychological, reference, and economic factors on people’s interest in choosing Mitra Emas Financing at BJB Syariah KCP Jembatan Merah. The type of research used in this thesis is a quantitative methode. The processed data is in the form of partial and simultaneous data. Data analysis techniques used in this study using observation and questionnaires, data processing using SPSS. Based on the result of the study, it showed that culture ((X1), social (X2), personal (X3), psychological (X4), reference (X5), economics(X6), had an effect on Public Interest in BJB Syariah KCP Jembatan Merah Gold Partners Financing. This is evidenced by the value of t count > t table. Therefore ho is rejected and He is accepted. From the test results on the simultaneous research of cultural, social, personal, psychological, reference, and economic factors and real influence on people’s interest in gold partner financing. This is evidenced by the F count > F table (37.477 > 2.29) and the sig value of 0.000 < 0.05. So the calculation shows that the independent variables consist of culture, social, personal, psychological, reference, and economics.